Voimalla läpi jäämuurin: Suomalaisen talvimerenkulun historiaa Suomen merimuseossa - Pylsy-Komppa, Elina (Tekniikan Waiheita, 2015)
A new exhibition Voimalla liikkeelle! at The Maritime Museum of Finland in The Maritime Centre Vellamo in Kotka, tells the story of naval architect Karl Albin Johansson and the birth of Finnish icebreaker construction through the development and construction of the Finnish state icebreaker Voima, commissioned in 1954. This ship was the crowning achievement of Johansson’s career and the starting point for the Wärtsilä Helsinki Shipyard in specialising in icebreakers as the sole such shipyard in the world. The project relied on interwar develop-ment between the naval architect, the shipyard and the Finnish state. The review relies on the extensive Johansson archives held by the maritime museum and recently fully inventoried by the author. The collection is searchable through the Finnish archive, library and museum aggregate search service Finna at https://www.finna.fi/."